Supplementary Strategies for Organizational Resilience in the Times of Crises : A Literature Review - Damayanti, Ilma; Suryani, Indah Permata (Universitas Muhammadiyah Magelang, 2024)
This literature review explores complementary strategies for enhancing organizational resilience during crises. The study examines how innovation, dynamic capabilities, internal competencies, external support, and crisis-derived opportunities interact with resilience to help businesses survive and thrive in uncertain times. Through analysis of 26 Scopus-indexed articles from 1998 to 2024, the paper proposes an integrated model positioning organizational resilience as the core element, supported by innovation and dynamic capabilities as key enablers. Internal capabilities like networking and adaptability, along with external factors such as government support and digitalization, further reinforce resilience. Additionally, the study highlights how crises, despite their challenges, can drive positive transformation and growth when approached strategically. The proposed model suggests that maximizing these complementary elements collectively strengthens an organization's capacity to weather crises and emerge stronger. While providing valuable insights, the paper acknowledges limitations in its literature-based approach and calls for empirical testing across diverse contexts. This research contributes to a more holistic understanding of organizational resilience, offering a framework for businesses to develop comprehensive strategies for navigating crises and capitalizing on emergent opportunities.